PENINGKATAN HASIL BELAJAR SISWA SMP KELAS IX PADA MATERI PERSAMAAN KUADRAT MELALUI PEMBELAJARAN DARING DENGAN PENDEKATAN SAINTIFIK - Santi Syaadah; Muhammad Ghiyats Ristiana (IKIP Siliwangi, 2022)
This research is a classroom action research that aims to determine the improvement of students' mathematics learning outcomes after using a scientific approach to online learning. The research was carried out at SMP Negeri 8 Cimahi with the subjects of class IX students totaling 35 people. Collecting data in the form of student test results with a discussion of quadratic equations. This research was conducted in 2 cycles. Each cycle was carried out in 2 meetings. In the first cycle, the learning was less than optimal in applying the scientific approach and the students' motivation to learn mathematics was less. In the second cycle, the deficiencies that occurred in the first cycle were corrected. In cycle II, many students were able to solve the questions given, actively asked if there was something they did not understand and many students were able to participate in online learning using a scientific approach. The results of this study indicate that the scientific approach to online learning can be applied and an increase in each cycle has a good impact on grade IX students at SMP Negeri 8 Cimahi.